Pengaruh Konflik Dan Stress Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Indomarco Prismatama (Studi Kasus Pada Indomaret Baturaja) - Darman Syafei; Hilmi Wiranawata (Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of conflict and work stress on employee productivity at PT Indomaret Prismatama Data used secondary data. The analysis used is a classic assumption, multiple linear regression analysis, t test, F test and coefficient of determination analysis. T test results show that conflict (X1) affects the work productivity of employees and work stress also (X2) affects the work productivity of employees (Y) employees at PT Indomarco Prismatama Baturaja. The F test results found that work conflict and stress jointly affect the work productivity of employees (Y) at PT Indomarco Prismatama Baturaja. The magnitude of the contribution of conflict (X1) and work stress (X2) of 88.5% on the ups and downs of employee work productivity (Y) while the remaining 11.5% is influenced by other variables not included in the research model.